STRATEGI PENGEMBANGAN AGROWISATA BERBASIS ANALISIS SWOT DI UNIT USAHA AGRO MANDIRI - Suwardhana Adyaksa Anak Agung Putra; I Gusti Ngurah Apriadi Aviantara; I Wayan Widia (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2015)
The aims of this research was analyze the internal and external conditions to develop and recommend business development strategies on Agro Mandiri. This research was conducted in Agro Mandiri. The method used in this research was survey and in-depth interviews using a questionaire assistance. The data of resulting from survey and interviews were analyzed to obtain the formulation of strategies using Strengths, Weaknesses, Opportunities, Threaths (SWOT) analysis. Assessment weighting and rating done by 5 experts. The results showed that there were 3 strengths, 6 weaknesses, 4 opportunities, and 3 threats. The results of the weighting and rating assessment were 3,65 for Internal Factor Evaluation (IFE) and 3,29 for External Factor Evaluation (EFE). This value indicates a strong position in the matrix Internal External (IE) with the strategy that should be done were intensive and integrative strategies. Based on the SWOT analysis matrix, there were 4 alternative strategies with 7 programs that will be used to agrotourism develop Agro Mandiri.